‘Almost true’: Peter Rindisbacher's early images of Rupert's Land, 1821–26 - Peers, L (Wiley, 2009)
This article examines early watercolours and sketches by Peter Rindisbacher, who in 1821, emigrated with his family from Switzerland to the Red River Settlement in Winnipeg, Canada. Rindisbacher's work has been praised, and made use of, for its detailed renderings of clothing and objects typical of the Northwestern fur trade. The article examines both the materiality of the images and the materiality within them, in order to understand his European mindset and training and consider their implications for the veracity of his work, which reflects European stereotypes of Aboriginal people. Viewers' responses to Rindisbacher's images are also explored, and the correlation between the assumption of veracity in these images and expectations about the ‘frontier’ is noted. Rindisbacher's images both reflect such expectations, and complicate them.